2015
DOI: 10.1124/jpet.115.225490
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glutathione Is Not Sufficient to Protect against Doxorubicin-Induced Nuclear Damage in Heart in Multidrug Resistance–Associated Protein 1 (Mrp1/Abcc1) Null Mice

Abstract: Cardiotoxicity is a major dose-limiting adverse effect of doxorubicin (DOX), mediated in part by overproduction of reactive oxygen species and oxidative stress. Abcc1 (Mrp1) mediates the efflux of reduced and oxidized glutathione (GSH, GSSG) and is also a major transporter that effluxes the GSH conjugate of 4-hydroxy-2-nonenal (HNE; GS-HNE), a toxic product of lipid peroxidation formed during oxidative stress. To assess the role of Mrp1 in protecting the heart from DOX-induced cardiac injury, wild-type (WT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
6
11
1
Order By: Relevance
“…We recently found that 72 hours after a single dose of DOX (15 mg/kg body weight, i.v. ), there is significantly more nuclear injury in the Mrp1 2/2 heart compared with the WT heart (Deng et al;2015). On the basis of these findings, we hypothesized that Mrp1 protects against DOX-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…We recently found that 72 hours after a single dose of DOX (15 mg/kg body weight, i.v. ), there is significantly more nuclear injury in the Mrp1 2/2 heart compared with the WT heart (Deng et al;2015). On the basis of these findings, we hypothesized that Mrp1 protects against DOX-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 84%
“…GS-HNE was somewhat elevated at 48 hours after DOX and significantly increased 2 weeks after the last dose of DOX, but this increase was similar in WT and Mrp1 2/2 mice. By contrast, after a single dose of DOX, GS-HNE was significantly decreased in WT mice relative to saline treatment, whereas there was no change in GS-HNE in Mrp1 2/2 mice (Deng et al, 2015). We have shown that in WT mice, a single dose of DOX (20 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations